Cooperative Student for Developing Students Character - Sukidjo, Sukidjo; Muhson, Ali; Mustofa, Mustofa (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2016)
Abstract: Cooperative Student for Developing Students Character. The purpose of this study was to analyze the implementation of cooperative student development model as a model as character education in Vocational High School (SMK). The samples of this study are 20 SMK in DIY. Cooperative Student development, as a model of character education, uses the Research and Development. This study managed to compile a guidebook of Cooperative Student development. The study also proved that the activities in student cooperatives were able to develop the character values such as kinship, independence, responsibility, and democracy.Keywords: Cooperative development, character education.Abstrak: Koperasi Sekolah Sebagai Wadah Pengembangan Karakter Siswa. Tujuan penelitian ini adalah menganalisis implementasi model pengembangan koperasi siswa (kopsis) sebagai model pendidikan karakter di SMK. Penelitian ini mengambil sampel sekolah sebanyak 20 SMK di Provinsi DIY. Pengembangan kopsis sebagai model pendidikan karakter menggunakan Research and Development. Penelitian ini berhasil menyusun buku panduan penerapan model pengembangan kopsis. Penelitian ini juga berhasil membuktikan bahwa kegiatan berkoperasi mampu menumbuhkan nilai karakter seperti kekeluargaan, kemandirian, tanggung jawab, dan demokrasi.Kata Kunci: Pengembangan Koperasi, pendidikan karakter